2020
DOI: 10.1016/j.msard.2020.101954
|View full text |Cite
|
Sign up to set email alerts
|

Matching-adjusted comparisons demonstrate better clinical outcomes in patients with relapsing multiple sclerosis treated with peginterferon beta-1a than with teriflunomide

Abstract: Background: Peginterferon beta-1a and teriflunomide are both first-line disease-modifying therapies (DMTs) approved for the treatment of relapsing multiple sclerosis (RMS); however, no head-to-head trials have directly compared their clinical efficacy. We performed a matching-adjusted comparison of individual patient data from the peginterferon beta-1a pivotal phase 3 study, ADVANCE, and its extension study, ATTAIN, with pooled aggregated data from the teriflunomide pivotal phase 3 studies, TEMSO and TOWER. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Our findings on ARRs from the real-world propensity score analysis of patients treated with peginterferon beta-1a vs. other platform DMTs are directionally similar to that found in 3 indirect comparisons of clinical trial data (Coyle et al, 2018;Scott et al, 2019;Newsome et al, 2020). An exception is that Coyle et al (2018) did find that peginterferon beta-1a was associated with a lower ARR than SC IFN beta-1a.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our findings on ARRs from the real-world propensity score analysis of patients treated with peginterferon beta-1a vs. other platform DMTs are directionally similar to that found in 3 indirect comparisons of clinical trial data (Coyle et al, 2018;Scott et al, 2019;Newsome et al, 2020). An exception is that Coyle et al (2018) did find that peginterferon beta-1a was associated with a lower ARR than SC IFN beta-1a.…”
Section: Discussionsupporting
confidence: 78%
“…This divergence in findings may be from differences in baseline disease severity (e.g., number of relapses in 1-3 prior years, number of lesions) among study populations, alongside other differences between trial populations and patients in real-world settings. The 3 indirect matching-adjusted comparisons of treatment efficacy across clinical trial patients also provided evidence that peginterferon beta-1a treatment is associated with less confirmed disability worsening than SC IFN beta-1a, GA, and teriflunomide (Coyle et al, 2018;Scott et al, 2019;Newsome et al, 2020). We used claims for durable medical equipment as a proxy for disability worsening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the proportion of patients with confirmed disability worsening at 108 weeks was significantly lower in the PEG IFNβ-1a group than the teriflunomide group, and that patients treated with PEG IFNβ-1a had lower annualized relapse rates at 108 weeks and 5 years compared to teriflunomide. 46 While these outcomes have been supported by other meta-analyses, there have been no randomized, head-to-head trial proving this.…”
Section: De-escalationmentioning
confidence: 96%
“…Some evidence suggests that IFNβ therapy may be a superior option to teriflunomide when considering a lowerefficacy treatment. A recent study by Newsome et al 46 performed a matching-adjusted comparison of patient data from the ADVANCE and ATTAIN trials evaluating PEG IFNβ-1a to the TEMSO and TOWER studies evaluating teriflunomide. The results showed that the proportion of patients with confirmed disability worsening at 108 weeks was significantly lower in the PEG IFNβ-1a group than the teriflunomide group, and that patients treated with PEG IFNβ-1a had lower annualized relapse rates at 108 weeks and 5 years compared to teriflunomide.…”
Section: De-escalationmentioning
confidence: 99%